Analisis Faktor-Faktor yang Mempengaruhi Kesejahteraan di Kawasan Indonesia Timur - Popy Ragilia Margashella; Arfida Boedirochminarni; Sri Budi Cantika Yuli (Universitas Muhammadiyah Bengkulu, 2025)
Economic development aims to improve the welfare of society through transformation in the political, economic, and socio-cultural sectors. The stages of development can be carried out by developing the economic sector and addressing various challenges faced. In 2023, most provinces in the Eastern Indonesia region have an HDI below the national average. Thus, the researchers aim to identify and analyze the impact of Years of Schooling Expectation, Open Unemployment Rate, Poverty Rate, and Gross Domestic Product on the Human Development Index as an indicator of Welfare in the Eastern Indonesia Region. This research uses secondary data obtained from the Central Statistics Agency with a time frame of 2015-2023 and employs the panel data regression analysis method. The research results indicate that the expected years of schooling and GDP have a significant positive impact on the Human Development Index (HDI) in the Eastern Indonesia region, while the open unemployment rate and the number of poor residents have a significant negative impact on the HDI in the Eastern Indonesia region. Simultaneously, all variables significantly affect the HDI in the Eastern Indonesia region, with an R-squared model value of 0.826543, indicating that approximately 82.65% of the variation in HDI can be explained by the independent variables in this model